Disparities in Recruitment and Screen Failure by Race and Ethnicity in the Harvard Aging Brain Study (HABS). (20th December 2022) - Levin, Raina; Vila‐Castelar, Clara; Samaroo, Aubryn H; Muniz, Martha C.; Martinez, Jairo E.; Gonzalez, Christopher; Garza‐Naveda, Ana Paola; Quiroz, Yakeel T.; Rentz, Dorene M.; Johnson, Keith A.; Sperling, Reisa A.
Abstract: Background: Despite progress, disparities in Alzheimer's Disease (AD) research participation continue to be a problem. Underrepresentation of certain racial and ethnic groups can result from several factors, including narrow recruitment strategies and strict exclusion criteria, and hinders our understanding of AD. We examined racial/ethnic differences in recruitment and screen failure in the Harvard Aging Brain Study (HABS), a longitudinal observational study, to elucidate these discrepancies. Method: We analyzed HABS screening data from September 2010 to December 2021. Eligible participants were 50‐90 years old, cognitively intact (based on CDR, Logical Memory, and MMSE scores), in stable physical health, and had a study partner who could answer questions about their daily functioning. Participants were categorized into four mutually exclusive racial/ethnic groups based on self‐report data: Hispanic/Latino, White, Black, and other (Asian, American Indian/Alaskan Native, >1 Race, or did not disclose). Screen fail reasons were divided into clinical/cognitive, MRI/PET contraindications, medical and psychiatric history, and other. Statistical analyses included chi‐square, odds ratio, and t‐tests. Result: The racial/ethnic breakdown of the 514 screened participants was 72.0% White, 14.0% Black, 10.9% Hispanic/Latino, and 3.1% other. Black participants had lower mean years of education than White participants (p < .05; Black, Mean [SD] = 14.28 [2.76]; White, 16.00 [2.96]). A total of 18.7% of participants screen failed with 17.8% of White, 19.4% of Black, and 28.6% of Hispanic/Latino participants (p > .05). Clinical/cognitive test scores were the most common reason for screen failure across all participants (41.7%), followed by medical history (26.0%). There were differences across racial/ethnic groups; compared with White participants, Black (odds ratio (OR), 2.6, 95% CI, 1.1‐5.6; p < .05) and Hispanic/Latino (OR, 2.7; 95% CI, 1.0‐6.1; p < .05) were more likely to meet exclusion criteria for cognition. Conclusion: While efforts have been made to broaden recruitment strategies, create a Spanish‐language cohort, and revise exclusion criteria, racial/ethnic differences in recruitment and screen failure of HABS participants persist. This reflects a continued need to identify more culturally appropriate cognitive tests, norms, and cutoffs. Discovering and analyzing disparities by race/ethnicity will inform future efforts to create inclusive cohorts, leading to more representative AD research.